Modern state of stocks for demersal and pelagic fishes on the shelf of Olyutorsky-Navarin area - A. B. Savin (Известия ТИНРО, 2021)
Stocks of demersal and pelagic fish species are assessed for the bottom layer over the outer shelf and upper continental slope between Cape Olyutorsky and Cape Navarin (northwestern Bering Sea) on the data of bottom trawl survey conducted aboard RV Professor Levanidov over the isobaths 20-400 m in the summer of 2019. The total biomass of demersal fish in the surveyed polygon was estimated as 682,262 t; the portion of pacific cod was 51.50 %, arrowtooth flounder — 9.80 %, great sculpin — 9.64 %, rock sole — 4.60 %, alaska skate — 4.57 %, flathead flounders — 2.56 %, yellow irish lord — 2.30 %, and < 2 % for other species. The total biomass of pelagic fish species in the bottom layer was estimated as 759,639 t (species-specific coefficients of catchability were used); the portion of adult walleye pollock was 85.12 %, its juveniles — 9.94 %, pacific herring — 4.67 %, and other pelagic species — 0.27 % in sum. Mean ratios of the species stock between the surveyed polygon and other areas of the northwestern Bering Sea, as the Gulf of Anadyr and the deeper continental slope (below 400 m), were evaluated using the data of bottom trawl surveys conducted in 2005-2017. Some species as yellow irish lord, saffron cod, pacific halibut, arrowtooth flounder, great sculpin, kamchatka flounder, rock sole, and aleutian skate distributed mostly within the polygon and their mean biomass in the outside areas varied from 0.5 % to 69.2 % relative to the biomass in the polygon surveyed in 2019. On the contrary, the portions of pacific cod, greenland halibut, alaska skate, and walleye pollock were larger outside the polygon — from 102.9 to 190.4 %, and almost entire stocks were in the outside areas for alaska plaice, flathead flounders, and pacific herring — from 533.4 % to 1380.5 % relative to the biomass accounted within the polygon. The stocks assessed in 2019 reflected both the state of populations and their spatial and bathymetric redistribution, mostly because of the St. Lawrence Cold Water Pool shrinkage at the bottom of the Gulf of Anadyr. The stocks fluctuations are reasoned mainly by natural factors, rather than fishery impact.